Tribological Application of Nanocomposite Additives in Industrial Oils - Milan Bukvić; Sandra Gajević; Aleksandar Skulić; Slobodan Savić; Aleksandar Ašonja; Blaža Stojanović (Lubricants, 2023)
The demand for an improvement in the tribological properties of lubricants used in various industrial plants, the automotive industry, and other power transmissions has resulted in the development of a whole family of improved lubricants based on nanotechnology. Especially important are nanotube additives, which significantly improve the tribological properties of lubricants, primarily by reducing the friction coefficient and wear of the coupled elements but also by reducing the temperature load and increasing the stability of the oil film between the lubricated surfaces. The properties of nanotube-based additives were further improved using elements such as metal oxides and compounds based on titanium, molybdenum, aluminum, etc. This paper presents the results obtained in the field of research and application of nanocomposite lubricant additives. It also gives a partial comparative analysis of the research conducted in this field. The primary goal of this paper is to analyze the research results in the field of the application of nanotubes in lubricants and to indicate the importance of their application, such as improving the tribological properties of machines and reducing power losses. Furthermore, this paper shows the negative impact of nanoparticles on the environment and human health and the costs of applying some types of nanoparticles.